2018
DOI: 10.4103/ccd.ccd_756_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of salivary cortisol levels in bruxism patients before and after using soft occlusal splint: An in vivo study

Abstract: Introduction:Bruxism is defined as a nonfunctional activity or a parafunctional habit characterized by the unconscious repetitive motion of clenching and/or grinding of the teeth. Soft occlusal splints have been considered as the first-line strategy for treating nocturnal bruxism. Cortisol is a major steroid hormone secreted by fascicular zone of the adrenal cortex, belonging to the glucocorticosteroidal group of hormones. Clinical studies have shown that when humans are placed under stress, the hypothalamic–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are few studies evaluating the e cacy of treatment for bruxism using biomarkers. Sriharsha et al [44] reported that cortisol levels decreased in 70% of subjects after the use of soft occlusal splint. In our study, cortisol levels decreased after treatment in both Botox and occlusal splint groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies evaluating the e cacy of treatment for bruxism using biomarkers. Sriharsha et al [44] reported that cortisol levels decreased in 70% of subjects after the use of soft occlusal splint. In our study, cortisol levels decreased after treatment in both Botox and occlusal splint groups.…”
Section: Discussionmentioning
confidence: 99%
“…vacuum-formed thermoplastic materials such as polypropylene and polyethylene [12][13][14][15]. Conversely, a few reports have revealed some clinical benefits of soft occlusal splints such as effectiveness in treating myogenous temporomandibular disorders [16] and enhanced comfort for occlusal splint wearers [17]. In additive manufacturing, photosensitive materials are polymerized using light from the luminous source of a 3D printer.…”
mentioning
confidence: 99%